2021
DOI: 10.1111/ajt.16105
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral immunotherapy with anti-PD-1 and TLR9 agonist induces systemic antitumor immunity without accelerating rejection of cardiac allografts

Abstract: Immune checkpoint inhibitors, such as programmed cell death 1 (PD-1) blockades, have revolutionized the field of cancer immunotherapy. However, there is a growing concern whether PD-1 inhibitors can be administered safely to transplant recipients with advanced cancer, as the T cells activated by checkpoint inhibitors may become reactive not only toward tumor antigens but also toward donor alloantigen, thereby resulting in allograft rejection. Here, immunotherapy with anti-PD-1/toll like receptor 9 agonist was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(132 reference statements)
0
2
0
Order By: Relevance
“…Recently, there have been many clinical trials focusing on the clinical application of intratumoral immune checkpoint inhibitors with encouraging preliminary results, including the phase I clinical trial of cemiplimab, an intratumoral anti-PD-1 agent (NCT03889912), and the phase I clinical trial of Nivolumab, an intratumoral anti-PD-1 agent (NCT03316274), Phase II and Phase III clinical trials of the intratumoral anti-PD-1 drug ipilimumab or Nivolumab in combination with the anti-CTLA-4 drug Ipilimumab (NCT04090775, NCT03755739), anti-CD40 inhibitor Selicrelumab in combination with the anti-PD-L1 inhibitor Atezolizumab (NCT03892525) and other ( 56 ). For patients with allogeneic transplants, intratumoral anti-PD-1 treatment combined with TLR9 agonist can ensure a strong anti-tumor immune response while avoiding severe transplant rejection caused by systemic immunotherapy, reflecting the unique effectiveness and safety of intratumoral injection ( 57 ). In contrast, the immunosuppressive TME may be responsible for the low systemic immune response and immune checkpoint inhibitor therapy failure.…”
Section: Application Of Intratumoral Immunotherapymentioning
confidence: 99%
“…Recently, there have been many clinical trials focusing on the clinical application of intratumoral immune checkpoint inhibitors with encouraging preliminary results, including the phase I clinical trial of cemiplimab, an intratumoral anti-PD-1 agent (NCT03889912), and the phase I clinical trial of Nivolumab, an intratumoral anti-PD-1 agent (NCT03316274), Phase II and Phase III clinical trials of the intratumoral anti-PD-1 drug ipilimumab or Nivolumab in combination with the anti-CTLA-4 drug Ipilimumab (NCT04090775, NCT03755739), anti-CD40 inhibitor Selicrelumab in combination with the anti-PD-L1 inhibitor Atezolizumab (NCT03892525) and other ( 56 ). For patients with allogeneic transplants, intratumoral anti-PD-1 treatment combined with TLR9 agonist can ensure a strong anti-tumor immune response while avoiding severe transplant rejection caused by systemic immunotherapy, reflecting the unique effectiveness and safety of intratumoral injection ( 57 ). In contrast, the immunosuppressive TME may be responsible for the low systemic immune response and immune checkpoint inhibitor therapy failure.…”
Section: Application Of Intratumoral Immunotherapymentioning
confidence: 99%
“…Dang et al . [ 106 ] showed that intratumor, but not systemic, immunotherapy with anti‐PD‐1/toll like receptor 9 agonist promoted potent antitumor responses but did not accelerate allograft rejection in mice recipients of heart allografts with cancer, provided that the tumor and cardiac allograft shared major histocompatibility complex (MHC). However, the antitumor effect was compromised by maintenance immunosuppression with CyA, highlighting the importance of finding an optimal balance between antitumor and antigraft immunity.…”
Section: Looking Into the Futurementioning
confidence: 99%